Model pathway diagrams for the representation of mathematical models - Müller, Dennis; Kohlhase, Michael; Koprucki, Thomas; Tabelow, Karsten; Rabe, Florian (Optical and Quantum Electronics, 2018)
Mathematical models are the foundation of numerical simulation of optoelectronic devices. We present a concept for a machine-actionable as well as human-understandable representation of the mathematical knowledge they contain and the domainspecific knowledge they are based on. We propose to use theory graphs to formalize mathematical models and model pathway diagrams to visualize them. We illustrate our approach by application to the van Roosbroeck system describing the carrier transport in semiconductors by drift and diffusion. We introduce an approach for the block-based composition of models from simpler components.
Keywords: Mathematical models; Research data; Model pathway diagrams; Drift-diffusion equations